Application of Polypyrrole Cellulose Nanocrystalline Composite Conductive Material in Garment Design - Si Su; Shaoying Hu; Qi Liu (Advances in Materials Science and Engineering)
The Chinese nation has a long cultural history and has deep attainments in food, clothing, art, and other cultural fields. With the development of science, technology, economy, and culture, new materials continue to appear, providing new ideas for clothing design. Polypyrrole is a common conductive polymer. The pure pyrrole monomer presents a colorless oily liquid at room temperature, slightly soluble in water and nontoxic. Nanocrystals, also called nanoscale crystals, use high-energy polymer spheres to pack calcium, magnesium ions, and bicarbonate in water to produce a water-insoluble crystal structure. Conductive composite materials mainly refer to composite conductive polymer materials, which are composed of polymers and various conductive substances through a certain composite method. This article aims to study the application of polypyrrole cellulose nanocrystalline composite conductive material in clothing design. Starting from the structural characteristics of the polypyrrole cellulose nanocrystalline composite conductive material, this article uses case analysis to study deeply the suitable polypyrrole cellulose nanocrystalline composite conductive material. This article can effectively use the innovative application method of its appearance style, so as to realize its application in clothing design. Starting from the functional properties of the polypyrrole cellulose nanocrystalline composite conductive material, the specific application of the polypyrrole cellulose nanocrystalline composite conductive material in different clothing designs is analyzed. Combining the postmodernist clothing style characteristics, aesthetic habits, and the characteristics of polypyrrole cellulose nanocrystalline composite conductive materials, this paper studies the innovative style design of polypyrrole cellulose nanocrystalline composite conductive materials. The experimental results in this paper show that when the reaction time is 2 min, the reaction rate at this time is zero, indicating that this time is in the initial stage of the reaction. After 4 minutes, as the reaction time increases, the reaction rate shows an increasing trend; when the reaction time is longer than 10 minutes, the reaction rate increases slowly and has a downward trend, which indicates the end of the reaction. The highest average reaction rate is about 7.5 mg/min.